2021
DOI: 10.3389/fendo.2021.716082
|View full text |Cite|
|
Sign up to set email alerts
|

Lateral Lymph Node Metastases in T1a Papillary Thyroid Carcinoma: Stratification by Tumor Location and Size

Abstract: ObjectiveTo analyze the incidence and risk factors for lateral lymph node metastases (LNMs) in T1a papillary thyroid carcinoma (PTC) with a focus on tumor location and size.Materials and MethodsThe incidence of lateral LNM in 345 cases of T1a PTC was retrospectively analyzed. Univariate and multivariate analyses were performed to assess the relationships between lateral LNM and clinicopathological characteristics.ResultsThe incidence of skip metastasis to lateral LNM in T1a PTC located in the upper lobe was 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…Nuclear atypia has been widely analyzed for its reliability in predicting malignancy in AUS/FLUS nodules. Lim et al (13) The BRAF V600E mutation is the most common genetic alteration in thyroid cancer, it could even occur in 82.0% of T1a PTCs (25). Suh et al (9) reported that the BRAF V600E mutation was the second most influential independent predictor of malignancy in AUS/FLUS nodules and if combined with the Korean Thyroid Imaging Reporting and Data System, it could reduce unnecessary surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear atypia has been widely analyzed for its reliability in predicting malignancy in AUS/FLUS nodules. Lim et al (13) The BRAF V600E mutation is the most common genetic alteration in thyroid cancer, it could even occur in 82.0% of T1a PTCs (25). Suh et al (9) reported that the BRAF V600E mutation was the second most influential independent predictor of malignancy in AUS/FLUS nodules and if combined with the Korean Thyroid Imaging Reporting and Data System, it could reduce unnecessary surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The BRAF V600E mutation is the most common genetic alteration in thyroid cancer, it could even occur in 82.0% of T1a PTCs ( 25 ). Suh et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have focused on the association between tumor location and the region of LNM ( 16 , 17 ), indicating that the upper portion of the thyroid could be a vital risk factor for lateral LNM (LLNM) in PTC patients. However, what caused us to think was, when we only focused on the upper portion PTC, which risky group of these patients would suffer LLNM and would they have a higher risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…In general, distribution of PTC is more in female gender 25 (61%) and age group <55 years old, 30 (73.2%) in this study as compared to other study are predominant female gender and younger age group from 20-55 years [23]. However, ATA instructions, patients who have tumor stage T3 or T4 with negative cervical lymph nodes metastasis, need prophylactic central cervical lymph node dissection [17] and FNA is indicated when size of thyroid nodules ≥1 cm to diagnosis the thyroid cancer or can used when size of thyroid nodules <1 cm in association with extrathyroid invasion or probability LLN metastasis [24] as involves in the present study. Furthermore, surgical removal of central lymph nodes is obligatory in patient with PTC who has lateral LN metastasis to preclude cancer recurrence and skip metastasis [13].…”
Section: Discussionmentioning
confidence: 66%